Bradykinin Type 1 Receptor – Inducible Nitric Oxide Synthase: A New Axis Implicated in Diabetic Retinopathy - Othman, Rahmeh; Vaucher, Elvire; Couture, Réjean (Frontiers in Pharmacology, 2019)
Compelling evidence suggests a role for the inducible nitric oxide synthase, iNOS, and the bradykinin type 1 receptor (B1R) in diabetic retinopathy, including a possible control of the expression and activity of iNOS by B1R. In diabetic retina, both iNOS and B1R contribute to inflammation, oxidative stress and vascular dysfunction. The present study investigated whether inhibition of iNOS has any impact on inflammatory/oxidative stress markers and on the B1R-iNOS expression, distribution and action in a model of type I diabetes. Diabetes was induced in 6-week-old Wistar rats by streptozotocin (65 mg.kg-1, i.p.). The selective iNOS inhibitor 1400W (150 µg.10µl-1) was administered twice a day by eye-drops during the second week of diabetes. The retinae were collected 2 weeks after diabetes induction to assess the protein and gene expression of markers by Western blot and qRT-PCR, the distribution of iNOS and B1R by fluorescence immunocytochemistry, and the vascular permeability by the Evans Blue dye technique. Diabetic retinae showed enhanced expression of iNOS, B1R, carboxypeptidase M (involved in the biosynthesis of B1R agonists), IL-1β, TNF-α, vascular endothelium growth factor A (VEGF-A) and its receptor, VEGF-R2, nitrosylated proteins and increased vascular permeability. All those changes were reversed by treatment with 1400W. Moreover, the additional increase in vascular permeability in diabetic retina induced by intravitreal injection of R-838, a B1R agonist, was also prevented by 1400W. Immunofluorescence staining highlighted strong colocalization of iNOS and B1R in several layers of the diabetic retina, which was prevented by 1400W. This study suggests a critical role for iNOS and B1R in the early stage of diabetic retinopathy. B1R and iNOS appear to partake in a mutual auto-induction and amplification loop to enhance nitrogen species formation and inflammation in diabetic retina. Hence, B1R-iNOS axis deserves closer scrutiny in targeting diabetic retinopathy.